Effect of urea, compost, manure and bio-fertilizers on yield, percentage and composition of fatty acids of sesame seed oil (Sesamum indicum L.) - Ganjineh, Esmaeil; Babaii, Farzad; Mozafari, Afshin; Mirzaei Heydari, Mohammad; Naseri, Rahim (Cellular and Molecular Biology, 2019)
This study was carried out in Iran during two growing seasons 2016-2017. Sesame is one of the earliest oilseed plants, high oil percentage and high content of unsaturated fatty acids, especially oleic acid and linoleic acid, have led to an increase in the nutritional quality of sesame oil. Accordingly, a two-year experiment was conducted as factorial based on randomized complete block design with three replications. The evaluated factors included four levels of urea as nitrogen fertilizer (0, 33, 66 and 100% of plant requirement), three kinds of organic fertilizer (manure, vermicompost and control) and four kinds of biofertilizers (Azosperillum, Azotobacter, Azosperillum +Azotobacter and control). At the end of the growing season, seed yield, percentage and yield of seed oil and fatty acids composition (oleic acid, linolenic acid, linoleic acid, stearic acid and palmitic acid) were measured. The results showed that the effect of different levels of nitrogen, organic and biological fertilizers on all studied traits was significant in two years of experiment and in all three environments (control, manure and compost). Vermicompost fertilizer and Azosperillum + Azotobacter have a more favorable effect on traits than other levels of each of these fertilizers, but nitrogen fertilizer levels have different effects on different traits. The highest seed yield (1298 kg ha-1) was obtained for control environment in 100% nitrogen application, for manure environment in 33% nitrogen application (1565 kg ha-1) and for compost environment in 66% nitrogen application (1799 kg ha-1).